Proteins associated with cork formation in Quercus suber L. stem tissues. - Ricardo, Cândido P P; Martins, Isabel; Francisco, Rita; Sergeant, Kjell; Pinheiro, Carla; Campos, Alexandre; Renaut, Jenny; Fevereiro, Pedro (Journal of proteomics, 2011)
Cork (phellem) formation in Quercus suber stem was studied by proteomic analysis of young shoots of increasing age (Y0, Y1 and Y4) and recently-formed phellem (Y8Ph) and xylem (Y8X) from an 8-year-old branch. In this study 99 proteins were identified, 45 excised from Y8X and 54 from Y8Ph. These ones, specifically associated with phellem, are of "carbohydrate metabolism" (28%), "defence" (22%), "protein folding, stability and degradation" (19%), "regulation/signalling" (11%), "secondary metabolism" (9%), "energy metabolism" (6%), and "membrane transport" (2%). The identification in phellem of galactosidases, xylosidases, apiose/xylose synthase, laccases and diphenol oxidases suggests intense cell wall reorganization, possibly with participation of hemicellulose/pectin biosynthesis and phenol oxidation. The identification of proteasome subunits, heat shock proteins, cyclophylin, subtilisin-like proteases, 14-3-3 proteins, Rab2 protein and enzymes interacting with nucleosides/nucleic acids gives additional evidence for cellular reorganization, involving cellular secretion, protein turnover regulation and active control processes. The high involvement in phellem of defence proteins (thioredoxin-dependent peroxidase, glutathione-S-transferase, SGT1 protein, cystatin, and chitinases) suggests a strong need for cell protection from the intense stressful events occurring in active phellem, namely, desiccation, pests/disease protection, detoxification and cell death. Identically, highly enhanced defence functions were previously reported for potato periderm formation.
Keywords: Cork; Phellem formation; Proteomics; Quercus suber stem; Suberisation